Venlo, surprisingly medieval (Bulletin KNOB, 2004)
For a long time it was thought that in the North-Limburg town of Venlo few houses from before the nineteenth century survived, although the town centre dates back to the Middle Ages. On the one hand, this idea was caused by incomplete inventories in the past, when it was chiefly the facades of houses that were looked at. On the other hand, parts of the town were severely damaged during the Second World War and the reconstruction and redevelopment work made the impression that just a small historical area had been preserved.However, a recent, rough inventory of the town centre, which also took the structures behind the facades into account, showed that there were sixty late-medieval buildings and thirty buildings possibly containing medieval remains. Further building-historical research in some of these buildings confirmed the selection of the inventory drawn up. Markt 24 and 26, two buildings on the market square of Venlo, were studied and in both cases they turned out to be latemedieval.Markt 24 is originally a fifteenth-century mercantile house which was extended in the sixteenth century and acquired a side house. Markt 26 was also extended in the sixteenth century, but it had a public function (for instance, as a reception hall), judging from the first floor with the remains of a sixteenth-century fireplace and several decorated bolsters.The changes to both buildings seem to be connected with the increased importance of the Markt in the sixteenth century. In that period the town centre moved from Oude Markt on the river Maas to the present Markt and obtained a higher status. This also had consequences for Houtstraat, situated behind the Markt, which initially was an important commercial street leading to Oude Markt, but in the course of the sixteenth and seventeenth centuries changed into a service providing street. Thus the former mercantile houses changed as well.Houtstraat 9, previously a tall mercantile house with a gable on the street was combined under one single roof with its side house and adjacent premises no. 11 and probably acquired a brewery function. A similar process took place for the adjacent premises Houtstraat 13.On the basis of this rough inventory and the building-historical studies three types of houses are to be distinguished in Venlo so far: a large double house, four or more bays wide with a dividing wall up to the roof; a large, deep mercantile house with a gable on the street and thirdly, a smaller, deep mercantile house with low floors. Future research in Venlo should result in more information on the types of houses and the historical development of the town. Further research may also lead to better protection of the premises, which at present is rather arbitrary and not based on any structured study.